2018
DOI: 10.1166/jnn.2018.14957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermetallic Compound Formation in Al/Cu Clad Material Fabricated by Differential Speed Rolling

Abstract: In this study, the microstructure and mechanical property of Al/Cu clad material fabricated by differential speed rolling at room temperature were evaluated. Al and Cu plates were prepared and mechanically cladded at a differential speed ratio of 2:1 between the upper and lower rolls. Post- heat-treatment was carried out after the mechanical cladding at 400 °C for 60 min to induce the formation of intermetallic compound layers at the bonded interface of Al/Cu. As a result, differential speed rolling afforded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to the Al-Cu binary phase diagram as shown in Figure 4, there may form some intermetallic phases in the fusion zone and the interface zone during the welding process. The intermetallic phases could be mainly Al 4 Cu 9 , Al 2 Cu, and AlCu, 2,20,[24][25][26] which were highlighted in the diagram using the red lines C 1 , C 2 , and C 3 (Figure 4). As the temperature drops (548 C < T < 1083 C), based on the binary phase diagram, the Al 4 Cu 9 , Al 2 Cu, and AlCu could be formed in the molten pool.…”
Section: Coupling Interaction Between Electron Beam and Al-cu Bimetallic Sheetmentioning
confidence: 99%
“…According to the Al-Cu binary phase diagram as shown in Figure 4, there may form some intermetallic phases in the fusion zone and the interface zone during the welding process. The intermetallic phases could be mainly Al 4 Cu 9 , Al 2 Cu, and AlCu, 2,20,[24][25][26] which were highlighted in the diagram using the red lines C 1 , C 2 , and C 3 (Figure 4). As the temperature drops (548 C < T < 1083 C), based on the binary phase diagram, the Al 4 Cu 9 , Al 2 Cu, and AlCu could be formed in the molten pool.…”
Section: Coupling Interaction Between Electron Beam and Al-cu Bimetallic Sheetmentioning
confidence: 99%
“…It was found that Al 2 Cu, AlCu and Al 4 Cu 9 were formed at the interface after 2000 h of annealing at 150 o C. The same IMCs were also detected by F. Moisy et al [13] in the early stage of the reactive interdiffusion of CCA wires annealed at 300-350 o C using in-situ TEM. Only two IMCs (Al 2 Cu and Al 4 Cu 9 ) were found in Al/Cu clad material fabricated by differential speed rolling followed by a post heat treatment at 400 o C for 60 min [14]. Therefore, the types and amounts of IMCs at the Al/Cu interface are closely related to the preparation technology and the corresponding heat treatment.…”
Section: Introductionmentioning
confidence: 99%